A pharmacokinetics and safety phase 1/1b study of oral ixazomib in patients with multiple myeloma and severe renal impairment or end‐stage renal disease requiring haemodialysis. (16th May 2016) - Gupta, Neeraj; Hanley, Michael J.; Harvey, R. Donald; Badros, Ashraf; Lipe, Brea; Kukreti, Vishal; Berdeja, Jesus; Yang, Huyuan; Hui, Ai‐Min; Qian, Mark; Zhang, Xiaoquan; Venkatakrishnan, Karthik; et al.
Summary: Renal impairment (RI) is a major complication of multiple myeloma (MM). This study aimed to characterize the single‐dose pharmacokinetics (PK) of the oral proteasome inhibitor, ixazomib, in cancer patients with normal renal function [creatinine clearance (CrCl) ≥90 ml/min; n  =   20), severe RI (CrCl <30 ml/min; n  =   14), or end‐stage renal disease requiring haemodialysis (ESRD; n  =   7). PK and adverse events (AEs) were assessed after a single 3 mg dose of ixazomib. Ixazomib was highly bound to plasma proteins (~99%) in all renal function groups. Unbound and total systemic exposures of ixazomib were 38% and 39% higher, respectively, in severe RI/ESRD patients versus patients with normal renal function. Total ixazomib concentrations were similar in pre‐ and post‐dialyser samples collected from ESRD patients; therefore, ixazomib can be administered without regard to haemodialysis timing. Except for anaemia, the incidence of the most common AEs was generally similar across groups, but grade 3 and 4 AEs were more frequent in the severe RI/ESRD groups versus the normal group (79%/57% vs. 45%), as were serious AEs (43%/43% vs. 15%). The PK and safety results support a reduced ixazomib dose of 3 mg in patients with severe RI/ESRD.